Non-English Major Students Perception Toward the Teaching of English as a Compulsory Subject - Bahar, Bahar -; Husain, Dahlia (English Department, Universitas Negeri Surabaya, 2021)
English as a compulsory subject in university means that students from various majors are mandated to take English as one of their subjects in university. This research aims to investigate students perceptions toward the teaching of English as a compulsory subject at University. Despite many research have been conducted related to the subject, it seems salient to shed some light on this area especially due to the importance of mastery of the English language these days. The result of the research showed that students have a positive attitude toward the teaching of the English language as a compulsory subject. One of the most important discoveries lies in the students being motivated when the English being taught is closely related to their major. Last but not the least, due to some limitation of the studies suggestion for further research is expected.Keywords: perception, teaching, Compulsory subject